Jahrbuch für Wirtschaftsgeschichte / Economic History Yearbook (Akademie Verlag, 1960)
The Economic History Yearbook is a forum for scientific discussion about economic development, the logic of the market, as well as the social and cultural contexts of economic activity from the 16th century to the present. Geographically, it focuses on Europe and especially on Germany, emphasizing comparative perspectives.